The Mathematical Structure of the Space of Test Functions - Zohra Farnana,; Thuraya Rkhayes, (AlQalam Journal of Medical and Applied Sciences, 2025)
This paper aims to provide a simple and clear presentation of the mathematical structure of the space of test functions, highlighting the essential definitions, illustrative examples, and construction methods using the concept of convolution. These functions form the foundation of distribution theory and weak derivatives.